1998
DOI: 10.1111/j.1348-0421.1998.tb02284.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of the Amplicor PCR Assay for Initial Diagnosis and Assessment of Treatment Response for Pulmonary Tuberculosis

Abstract: We evaluated the Amplicor PCR assay as an initial diagnostic tool on the basis of clinical diagnosis, and assessed this assay as a follow-up test for patients with pulmonary tuberculosis during chemotherapy. Of the 208 specimens from 155 patients who were bacteriologically and/or clinically diagnosed with active tuberculosis before chemotherapy, 144 were Amplicor PCR-positive (sensitivity, 69.2%), which was equal to the results of culturing. Among 89 specimens which showed positive results by smear and culturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1
3

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
(11 reference statements)
2
3
1
3
Order By: Relevance
“…1 and 2). As found in previous studies [6][7][8]10], the results of both amplification assays remained positive longer than those of culture and smear. The collection of multiple sputum specimens improved the sensitivity of the assays but did not provide any benefit in clinical follow-up.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…1 and 2). As found in previous studies [6][7][8]10], the results of both amplification assays remained positive longer than those of culture and smear. The collection of multiple sputum specimens improved the sensitivity of the assays but did not provide any benefit in clinical follow-up.…”
Section: Resultssupporting
confidence: 64%
“…Moreover, like us, they found no correlation with the radiographic extent of disease. In contrast to the observations of Iinuma et al [7] and Yuen et al [14], we found no association between positive PCR and AMTDT results and initial sputum smear positivity, presence of cavitary disease or radiographic extent of tuberculosis. This is likely due to the heterogeneity of the study populations.…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…Other phospholipids. Antituberculophospholipid antibodies as serological markers have been reported to have a sensitivity and specificity of 86.9% and 100%, respectively (59). Acyltrehaloses are among the strongest antigenic glycolipids of M. tuberculosis.…”
Section: Nonproteinaceous Antigens As Diagnostic Agents In Elisamentioning
confidence: 99%
“…The NAA assay was performed according to the manufacturer's instructions (17). Briefly, samples were treated with Nacetyl-L-cysteine (NALC)-NaOH, lysed, and neutralized.…”
Section: Naa Proceduresmentioning
confidence: 99%